The Forecasting of Beef Cattle Population in Sinjai Regency, South Sulawesi, Indonesia - N. Rahmi; A. Asnawi; M. Ridwan (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2026)
One of the weaknesses of the livestock sector management in Indonesia, particularly in Sinjai Regency, is the lack of population data. The available data so far mostly consists of general beef cattle population data without clear population structure details. To understand the development of the beef cattle population, a forecasting approach based on various beef cattle population data in Sinjai Regency is necessary. This study aims to analyze the structure and dynamics of the beef cattle population and calculate the predicted population development of beef cattle in Sinjai Regency. This research uses a case study method with purposive location selection. The beef cattle population dynamics data were processed using the time series forecasting method, specifically exponential smoothing with α = 0.9, based on annual data over 10 years from 2015 to 2024. The results show that if the data behavior remains the same as the actual data from the past 10 years, the overall structure of the beef cattle population in Sinjai Regency consists of fewer male cattle compared to female cattle. The forecasted beef cattle population in Sinjai Regency for 2025–2034 varies and tends to increase year by year, except for a decline in population in 2033 due to technical constraints in the development of beef cattle by the community in the field. Keywords: Forecasting, Population, Beef Cattle, Sinjai Regency.